Antiarrhythmic therapy in the treatment of atrial fibrillation: yesterday, today, tomorrow - V. I. Podzolkov (Кардиоваскулярная терапия и профилактика, 2019)
Atrial fibrillation (AF) is the most common heart rhythm disorder encountered in clinical practice. Each year, the number of patients with AF significantly increases. It is associated with an increase of life expectancy and frequency of cardiovascular pathologies. Treatment of AF remains one of the most difficult tasks of modern cardiology. Currently, only a few antiarrhythmic drugs are available for use in Russia. More and more new attempts are being made to create a universal antiarrhythmic drug with a high level of anti-relapsing efficacy and adverse effects. The accumulated information suggests that the tactics of management of patients with arrhythmias will be intended to improving the new surgical and interventional treatment methods with use of anticoagulants and antiarrhythmic drugs. The multidisciplinary team of specialists on AF treatment should include an expert (cardiologist) in antiarrhythmic drug therapy, an interventional electrophysiologist, and a cardiac surgeon — master the technology of interventional or surgical ablation. Effective interaction of specialists of various levels will improve the results of rhythm control and prevention of complications in patients with AF.